The teaching difficulties of elementary school teachers of modern mathematics in some selected public schools in Manila - Subong, Nieva Liberia 1946- (1971)
The purpose of the study is to identify the teaching difficulties of elementary school teachers of modern mathematics in selected public elementary schools in Manila. Specifically, it seeks to know the teaching difficulties of elementary school teachers in modern mathematics, the nature of these difficulties, and how these difficulties vary according to educational qualification, grade level, teaching experience, attendance in orientation courses, and number of units in modern mathematics. The normative-survey method is used with the questionnaire and teacher-made test as the major tools.